Insect Physiology - T.B.Gour (Kalyani, 2004)
This book contain eleven chapters, describing the integument and all other physiological functions like the digestion, excretion, circulation, respiration nervous and muscular system, all of which are collectively responsible for the perpetution of the race and behavior of the insects.